Characterization of ionospheric irregularities over Vietnam and adjacent region for the 2008-2018 period - Nguyen Thanh, Dung; Le Huy, Minh; Amory-Mazaudier, Christine; Fleury, Rolland; Saito, Susumu; Nguyen Chien, Thang; Pham Thi Thu, Hong; Le Truong, Thanh; Nguyen Thi, Mai (Vietnam Journal of Earth Sciences, 2021)
This paper presents the variations of the rate of change of Total Electron Content (TEC) index (ROTI), characterizing the occurrence of ionospheric plasma irregularities over Vietnam and neighboring countries in the Southeast Asian region using the continuous GPS data during the 2008-2018 period. The results showed that the occurrence of strong ROTI in all stations is maximum in equinox months March/April and September/October and depends on solar activity. The ROTI is weak during periods of low solar activity and strong during periods of high solar activity. There is an asymmetry between the two equinoxes. During maximum and declining phases of 2014-2016, occurrence rates in March equinox are larger than in September equinox, but during the descending period of 2010-2011, the occurrence rates in September equinox at almost all stations are larger than in March equinox. The correlation coefficients between the monthly occurrence rate of irregularities and the F10.7 solar index at the stations in the equatorward EIA crest region are higher than at those in the magnetic equatorial and the poleward EIA crest regions. The irregularity occurrence is high in the pre-midnight sector, maximum between 2000 LT to 2200 LT. The maximum irregularity occurrence is located around 4-5° degrees in latitude equator-ward away from the anomaly crests.